Determination of Occupational Safety Culture and Job Satisfaction Levels of Factory Employees: Occupational Safety Culture and Job Satisfaction Levels of Employees (Turkey Health Literacy Journal, 2023)
The automotive sector has wide-ranging risks in terms of occupational safety. Workers in the vehicle maintenance and repair business in this sector may be exposed to serious physical and chemical hazards such as getting their hands and feet stuck between moving machine parts, hitting falling objects, fire and explosion. In this context, it is essential to establish and maintain a culture of occupational safety. Developing a culture of occupational safety, creating a positive and safe environment in the workplace is effective both in increasing job satisfaction and in reducing occupational accidents. Aim of the study was to determine the occupational safety culture and job satisfaction levels of factory employees and their relationship with effective factors. The study is descriptive. The data were collected by socio-demographic characteristics form and Occupational Safety Culture Scale and Minnesota Job Satisfaction Scale. 154 personnel participated in the study and the participation rate is 70%.The data were evaluated in SPSS 20.00 Package program. The mean age of the participants is 42.34±7.89. The youngest age to start work was 8. A significant positive correlation was found between “Management’s Security Commitment” and “Safety Behaviors” (p<0.05, r:0.520). 52% of the employees witnessed a work accident. They stated that the most common cause of occupational accident was “indifference and inattention (58.4%).There was no significant difference between the job satisfaction of the employees and the status of having and witnessing a work accident (p> 0.005). As the age of the employees increased, their level of knowledge on risk analysis increased.The safety perceptions of single ones, the job satisfaction of youngs and university graduates were high. The more the management’s commitment to occupational safety practices, the higher the safe behavior of the employees.According to this, the importance of occupational safety culture should be adopted by all employees and managers, creating a positive communication environment in the workplace by following international practices and increasing job satisfaction. It is recommended to carry out activities to increase